Mindfulness and Counselling - Grégoire, Simon; Baron, Charles; Baron, Louis (Canadian Journal of Counselling and Psychotherapy, 2012)
Recently, various authors have tried to establish bridges between counselling, psychotherapy, and mindfulness, a construct partly inspired by Buddhism. In this article, this construct is first defined and three intervention programs aimed at developing mindfulness and promoting psychological health are presented. The principles and exercises on which these programs are based are discussed, showing how they can enrich the practice of career counsellors working with stressed, anxious, depressed, or burnout clients.